SUCCESSIVE DIFFERENTIATION (Text)

$\color {royalblue} {Notation\ of\ successive\ derivatives}:\ \hspace{20cm}$
$1.\ \frac{dy}{dx}\ =\ y_1\ =\ f^\prime(x)\ =\ D(y)$
$2.\ \frac{d^2y}{dx^2}\ =\ y_2\ =\ f^{\prime \prime}(x)\ =\ D^2(y)$
$\color {royalblue} {Differential Equation}:\ \hspace{20cm}$
$\color {royalblue} {Definition}:\ \hspace{20cm}$
$An\ equation\ containing\ differential\ coefficients\ is\ called\ differential\ equation.$
$\color {royalblue} {Examples}:\ \hspace{20cm}$
$1.\ \frac{dy}{dx}\ +\ y\ =\ x$
$2.\ x\frac{d^2y}{dx^2}\ +\ 2\ \frac{dy}{dx}\ =\ xy$
$\color {royalblue} {Order\ of\ the\ differential\ equation}:\ \hspace{20cm}$
$The\ order\ of\ the\ highest\ derivative\ in\ the\ differential\ equation$$is\ called\ order\ of\ the\ differential\ equation.$
$\color {royalblue} {Degree\ of\ the\ differential\ equation}:\ \hspace{20cm}$
$The\ power\ of\ the\ highest\ derivative\ in\ the\ differential\ equation$$is\ called\ the\ degree\ of\ the\ differential\ equation.$
$\color {royalblue} {Example}:\ \hspace{20cm}$
$\color {red} {Find\ the\ order\ and\ degree\ of}\ 7(\frac{d^2y}{dx^2})^2\ +\ 5\ (\frac{dy}{dx})^5\ +\ 7\ y\ =\ Sin\ x\ \hspace{15cm}$
$\color {blue}{Solution:}\ order\ =\ 2,\ degree\ =\ 2\ \hspace{15cm}$
$\color {royalblue} {Problems}:\ \hspace{20cm}$
$\color {purple} {Example\ 1:}\ \color {red} {Find\ \frac{d^2y}{dx^2}}\ if\ y\ =\ e^{2x}\ \hspace{15cm}$
$\color {blue}{Solution:}\ y\ =\ e^{2x}\ \hspace{15cm}$
$Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(y)\ =\ \frac{d}{dx}( e^{2x})\ \hspace{10cm}$
$\frac{dy}{dx}\ =\ 2\ e^{2x}\ \hspace{10cm}$
$Again\ Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(\frac{dy}{dx})\ =\ \frac{d}{dx}( 2\ e^{2x})\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ 4\ e^{2x}\ \hspace{10cm}$
$\color {purple} {Example\ 2:}\ \color {red} {Form\ the\ differential\ equation\ by\ eliminating\ the\ constant\ ‘a’\ in}\ x^2\ +\ y^2\ =\ a^2\ \hspace{15cm}$
$\color {blue}{Solution:}\ x^2\ +\ y^2\ =\ a^2\ \hspace{15cm}$
$Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}( x^2)\ +\ \frac{d}{dx}( y^2)\ =\ \frac{d}{dx}( a^2)\ \hspace{10cm}$
$2\ x\ +\ 2\ y\ \frac{dy}{dx}\ =\ 0\ \hspace{10cm}$
$2\ y\ \frac{dy}{dx}\ =\ -\ 2\ x\ \hspace{10cm}$
$\frac{dy}{dx}\ =\ -\ \frac{x}{y}\ \hspace{10cm}$
$\color {purple} {Example\ 3:}\ \color {red} {Eliminate\ the\ constant\ by\ differentiate\ twice}\ y\ =\ a\ Cos\ x\ +\ b\ Sin\ x\ \hspace{15cm}$
$\color {blue}{Solution:}\ y\ =\ a\ Cos\ x\ +\ b\ Sin\ x\ ——- (1)\hspace{15cm}$
$Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}( y)\ =\ a\ \frac{d}{dx}(Cos\ x)\ +\ b\ \frac{d}{dx}(Sin\ x) \hspace{10cm}$
$\frac{dy}{dx}\ =\ a\ (-\ Sin\ x)\ +\ b\ (Cos\ x)\ \hspace{10cm}$
$y_1\ =\ -\ a\ Sin\ x\ +\ b\ Cos\ x\ \hspace{10cm}$
$Again\ Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$y_2\ =\ -\ a\ Cos\ x\ -\ b\ Sin\ x\ \hspace{10cm}$
$y_2\ =\ -\ (a\ Cos\ x\ +\ b\ Sin\ x)\ \hspace{10cm}$
$y_2\ =\ – y\ \hspace{5cm}\ Using(1)$

$\color {purple} {Example\ 4:}\ \color {red} {Form\ a\ differential\ equation\ by\ eliminating\ the\ constant\ A\ and\ B\ from}\ y\ =\ A\ Cos\ 5x\ +\ B\ Sin\ 5x\ \hspace{15cm}$
$\color {blue}{Solution:}\ y\ =\ A\ Cos\ 5x\ +\ B\ Sin\ 5x\ ——- (1)\hspace{15cm}$
$Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}( y)\ =\ A\ \frac{d}{dx}(Cos\ 5x)\ +\ B\ \frac{d}{dx}(Sin\ 5x) \hspace{10cm}$
$\frac{dy}{dx}\ =\ A\ (-\ Sin\ 5x)\ (5)\ +\ B\ (Cos\ 5x)\ (5)\ \hspace{10cm}$
$y_1\ =\ -\ 5A\ Sin\ 5x\ +\ 5B\ Cos\ 5x\ \hspace{10cm}$
$Again\ Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$y_2\ =\ -\ 5A\ Cos\ 5x\ (5)\ -\ 5B\ Sin\ 5x\ (5)\ \hspace{10cm}$
$y_2\ =\ -\ 25(A\ Cos\ 5x\ +\ B\ Sin\ 5x)\ \hspace{10cm}$
$y_2\ =\ -\ 25\ y\ \hspace{5cm}\ Using(1)$
$\color {purple} {Example\ 5:}\ \color {red} {Find\ \frac{d^2y}{dx^2}}\ if\ y\ =\ Sec\ x\ \hspace{15cm}$
$\color {blue}{Solution:}\ y\ =\ Sec\ x\ \hspace{15cm}$
$Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(y)\ =\ \frac{d}{dx}( Sec\ x)\ \hspace{10cm}$
$\frac{dy}{dx}\ =\ Sec\ x\ Tan\ x\ \hspace{10cm}$
$Again\ Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(\frac{dy}{dx})\ =\ \frac{d}{dx}( Sec\ x\ Tan\ x)\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ Sec\ x\ \frac{d}{dx}(Tan\ x)\ +\ Tan\ x\ \frac{d}{dx}(Sec\ x)\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ Sec\ x\ Sec^2\ x\ +\ Tan\ x\ Sec\ x\ Tan\ x\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ Sec^3\ x\ +\ Tan^2\ x\ Sec\ x\ \hspace{10cm}$
$\color {purple} {Example\ 6:}\ \color {red} {Find\ \frac{d^2y}{dx^2}}\ if\ y\ =\ x^4\ -\ 3\ x^3\ +\ 6\ x^2\ +\ 2\ x\ +\ 1\ \hspace{15cm}$
$\color {blue}{Solution:}\ y\ =\ x^4\ -\ 3\ x^3\ +\ 6\ x^2\ +\ 2\ x\ +\ 1\ \hspace{15cm}$
$Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(y)\ =\ \frac{d}{dx}( x^4)\ -\ 3\ \frac{d}{dx}( x^3)\ +\ 6\ \frac{d}{dx}( x^3)\ +\ 2\ \frac{d}{dx}( x) +\ \frac{d}{dx}( 1)\ \hspace{10cm}$
$\frac{dy}{dx}\ =\ 4\ x^3\ -\ 3\ (x^2)\ +\ 6(3\ x^2)\ +\ 2(1)\ +\ 0\ \hspace{10cm}$
$\frac{dy}{dx}\ =\ 4\ x^3\ -\ 3\ x^2\ +\ 18\ x^2\ +\ 2\ \hspace{10cm}$
$Again\ Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(\frac{dy}{dx})\ =\ \frac{d}{dx}( 4\ x^3\ -\ 3\ x^2\ +\ 18\ x^2\ +\ 2)\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ 4\ \frac{d}{dx}(x^3)\ -\ 3\ \frac{d}{dx}(x^2)\ +\ 18\ \frac{d}{dx}(x^2)\ +\ \frac{d}{dx}(2)\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ 4\ 3(x^2)\ -\ 3(2\ x)\ +\ 18 (2\ x)\ +\ 0\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ 12\ x^2\ -\ 6\ x\ -\ 36\ x\ \hspace{10cm}$
$\color {purple} {Example\ 7:}\ \color {red} {Find\ \frac{d^2y}{dx^2}}\ if\ y\ =\ Sin\ 3\ x\ \hspace{15cm}$
$\color {blue}{Solution:}\ y\ =\ Sin\ 3\ x\ \hspace{15cm}$
$Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(y)\ =\ \frac{d}{dx}( Sin\ 3\ x)\ \hspace{10cm}$
$\frac{d}{dx}(y)\ =\ Cos\ 3\ x\ \frac{d}{dx}(3\ x)\ \hspace{10cm}$
$\frac{d}{dx}(y)\ =\ Cos\ 3\ x\ 3(1)\ \hspace{10cm}$
$\frac{d}{dx}(y)\ =\ 3\ Cos\ 3\ x\ \hspace{10cm}$
$Again\ Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(\frac{dy}{dx})\ =\ \frac{d}{dx}( 3\ Cos\ 3\ x)\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ 3\ \frac{d}{dx}(Cos\ 3\ x)\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ 3\ (-\ Sin\ 3\ x\ 3(1))\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ -\ 9\ Sin\ 3\ x\ \hspace{10cm}$
$\color {purple} {Example\ 8:}\ If\ y\ =\ x^2\ Sin\ x,\ \color {red} {find\ \frac{d^2y}{dx^2}}\ \hspace{15cm}$
$\color {blue}{Solution:}\ y\ =\ x^2\ Sin\ x\ \hspace{15cm}$
$Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(y)\ =\ \frac{d}{dx}( x^2\ Sin\ x)\ \hspace{10cm}$
$\frac{dy}{dx}\ =\ x^2\ \frac{d}{dx}(Sin\ x)\ +\ Sin\ x\ \frac{d}{dx}(x^2)\ \hspace{10cm}$
$\frac{dy}{dx}\ =\ x^2\ Cos\ x\ +\ Sin\ x\ 2\ x\ \hspace{10cm}$
$\frac{dy}{dx}\ =\ x^2\ Cos\ x\ +\ 2\ x\ Sin\ x\ \hspace{10cm}$
$Again\ Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(\frac{dy}{dx})\ =\ \frac{d}{dx}(x^2\ Cos\ x\ +\ 2\ x\ Sin\ x)\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ \frac{d}{dx}(x^2\ Cos\ x)\ +\ 2\ \frac{d}{dx}(x\ Sin\ x)\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ x^2\ \frac{d}{dx}(Cos\ x)\ +\ Cos\ x\ \frac{d}{dx}(x^2)\ +\ 2[x\ \frac{d}{dx}(Sin\ x)\ +\ Sin\ x\ \frac{d}{dx}(x)]\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ x^2\ (-\ Sin\ x)\ +\ Cos\ x\ (2\ x)\ +\ 2[x\ Cos\ x\ +\ Sin\ x\ (1)]\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ -\ x^2\ Sin\ x\ +\ 2\ x\ Cos\ x\ +\ 2\ x\ Cos\ x\ +\ 2\ Sin\ x\ \hspace{10cm}$
$\frac{d^2y}{dx^2}\ =\ -\ x^2\ Sin\ x\ +\ 4\ x\ Cos\ x\ +\ 2\ Sin\ x\ \hspace{10cm}$
$\color {purple} {Example\ 9:}\ If\ y\ =\ x^2\ Sin\ x,\ \color {red} {prove\ that\ x^2\ y_2\ -\ 4\ x\ y_1\ +\ (x^2\ +\ 6)y}\ =\ 0\ \hspace{15cm}$
$(OR)$
$If\ y\ =\ x^2\ Sin\ x,\ \color {red} {prove\ that\ x^2\ \frac{d^2y}{dx^2}\ -\ 4\ x\ \frac{dy}{dx}\ +\ (x^2\ +\ 6)y}\ =\ 0\ \hspace{15cm}$
$\color {blue}{Solution:}\ y\ =\ x^2\ Sin\ x\ \hspace{15cm}$
$Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(y)\ =\ \frac{d}{dx}( x^2\ Sin\ x)\ \hspace{10cm}$
$\frac{dy}{dx}\ =\ x^2\ \frac{d}{dx}(Sin\ x)\ +\ Sin\ x\ \frac{d}{dx}(x^2)\ \hspace{10cm}$
$y_1\ =\ x^2\ Cos\ x\ +\ Sin\ x\ 2\ x\ \hspace{10cm}$
$y_1\ =\ x^2\ Cos\ x\ +\ 2\ x\ Sin\ x\ \hspace{10cm}$
$Again\ Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(y_1)\ =\ \frac{d}{dx}(x^2\ Cos\ x\ +\ 2\ x\ Sin\ x)\ \hspace{10cm}$
$y_2\ =\ \frac{d}{dx}(x^2\ Cos\ x)\ +\ 2\ \frac{d}{dx}(x\ Sin\ x)\ \hspace{10cm}$
$y_2\ =\ x^2\ \frac{d}{dx}(Cos\ x)\ +\ Cos\ x\ \frac{d}{dx}(x^2)\ +\ 2[x\ \frac{d}{dx}(Sin\ x)\ +\ Sin\ x\ \frac{d}{dx}(x)]\ \hspace{10cm}$
$y_2\ =\ x^2\ (-\ Sin\ x)\ +\ Cos\ x\ (2\ x)\ +\ 2[x\ Cos\ x\ +\ Sin\ x\ (1)]\ \hspace{10cm}$
$y_2\ =\ -\ x^2\ Sin\ x\ +\ 2\ x\ Cos\ x\ +\ 2 x\ Cos\ x\ +\ Sin\ x\ \hspace{10cm}$
$y_2\ =\ -\ x^2\ Sin\ x\ +\ 4\ x\ Cos\ x\ +\ Sin\ x\ \hspace{10cm}$
$L.\ H.\ S\ =\ -\ x^2\ y_2\ -\ 4\ x\ y_1\ +\ (x^2\ +\ 6)y\ \hspace{10cm}$
$=\ -\ x^2\ (-\ x^2\ Sin\ x\ +\ 4\ x\ Cos\ x\ +\ Sin\ x)\ -\ 4\ x\ (x^2\ Cos\ x\ +\ 2\ x\ Sin\ x)\ +\ (x^2\ +\ 6)(x^2\ Sin\ x)\ \hspace{10cm}$
$=\ x^4\ Sin\ x\ -\ 4\ x^3\ Cos\ x\ -\ x^2\ Sin\ x)\ -\ 4\ x^3\ Cos\ x\ -\ 8\ x^2\ Sin\ x)\ +\ x^4\ Sin\ x+\ 6\ x^2\ Sin\ x\ \hspace{10cm}$
$=\ 0\ =\ R.\ H.\ S\ \hspace{10cm}$
$\color {purple} {Example\ 10:}\ \color {red} {If\ y\ =\ e^x\ Sin\ x,\ prove\ that}\ y_2\ -\ 2\ y_1\ +\ 2\ y\ =\ 0\ \hspace{15cm}$
$\color {blue}{Solution:}\ y\ =\ e^x\ Sin\ x\ —–\ (1)\ \hspace{15cm}$
$Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(y)\ =\ \frac{d}{dx}( e^x\ Sin\ x)\ \hspace{10cm}$
$\frac{dy}{dx}\ =\ e^x\ \frac{d}{dx}(Sin\ x)\ +\ Sin\ x\ \frac{d}{dx}(e^x)\ \hspace{10cm}$
$y_1\ =\ e^x\ Cos\ x\ +\ y\ using(1)\ —-\ (2)\ \hspace{10cm}$
$Again\ Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(y_1)\ =\ \frac{d}{dx}(e^x\ Cos\ x\ +\ y)\ \hspace{10cm}$
$y_2\ =\ \frac{d}{dx}(e^x\ Cos\ x)\ +\ \frac{d}{dx}(y)\ \hspace{10cm}$
$y_2\ =\ e^x\ \frac{d}{dx}(Cos\ x)\ +\ Cos\ x\ \frac{d}{dx}(e^x)\ +\ y_1\ \hspace{10cm}$
$y_2\ =\ e^x\ (-\ Sin\ x)\ +\ Cos\ x\ (e^x)\ +\ y_1\ \hspace{10cm}$
$y_2\ -\ y_1\ =\ -\ y\ +\ (y_1\ -\ y)\ using(2)\ \hspace{10cm}$
$y_2\ -\ y_1\ =\ -\ y\ +\ y_1\ -\ y\ \hspace{10cm}$
$y_2\ -\ y_1\ =\ -\ 2\ y\ +\ y_1\ \hspace{10cm}$
$y_2\ -\ y_1\ +\ 2\ y\ -\ y_1\ =\ 0\ \hspace{10cm}$
$y_2\ -\ 2\ y_1\ +\ 2\ y\ =\ 0\ \hspace{10cm}$
$\color {purple} {Example\ 11:}\ If\ y\ =\ a\ Cos(log\ x)\ +\ b\ Sin\ (log\ x),\ \color {red} {prove\ that\ x^2\ y_2\ +\ x\ y_1\ +\ y\ =\ 0}\ \hspace{10cm}$
$\color {blue}{Solution:}\ y\ =\ a\ Cos(log\ x)\ +\ b\ Sin\ (log\ x)\ —–\ (1)\ \hspace{15cm}$
$Differentiate\ both\ sides\ w.\ r.\ t.\ x\ \hspace{10cm}$
$\frac{d}{dx}(y)\ =\ \frac{d}{dx}( a\ Cos(log\ x)\ +\ b\ Sin\ (log\ x))\ \hspace{10cm}$
$\frac{dy}{dx}\ =\ a\ \frac{d}{dx}(Cos(log\ x))\ +\ b\ \frac{d}{dx}(Sin\ (log\ x))\ \hspace{10cm}$
$\frac{dy}{dx}\ =\ a\ (-\ Sin(log\ x))\ \frac{d}{dx}(log\ x)\ +\ b\ Cos(log\ x)\ \frac{d}{dx}(log\ x)\ \hspace{10cm}$
$y_1\ =\ -\ a\ Sin(log\ x)\ \frac{1}{x}\ +\ b\ Cos(log\ x)\ \frac{1}{x}\ \hspace{10cm}$
$y_1\ =\ \frac{1}{x}[-\ a\ Sin(log\ x)\ +\ b\ Cos(log\ x)]\ \hspace{10cm}$
$x\ y_1\ =\ -\ a\ Sin(log\ x)\ +\ b\ Cos(log\ x)\ \hspace{10cm}$
$Again\ Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(x\ y_1)\ =\ \frac{d}{dx}(-\ a\ Sin(log\ x)\ +\ b\ Cos(log\ x))\ \hspace{10cm}$
$x\ \frac{d}{dx}(y_1)\ +\ y_1\ \frac{d}{dx}(x)\ =\ -\ a\ \frac{d}{dx}(Sin(log\ x)\ +\ b\ \frac{d}{dx}(Cos(log\ x)\ \hspace{10cm}$
$x\ y_2\ +\ y_1\ (1)\ =\ -\ a\ (Cos(log\ x))\ \frac{d}{dx}(log\ x)\ +\ b\ (-\ Sin(log\ x)\ \frac{d}{dx}(log\ x)\ \hspace{10cm}$
$x\ y_2\ +\ y_1\ =\ -\ a\ Sin(log\ x)\ \frac{1}{x}\ -\ b\ Sin(log\ x)\ \frac{1}{x}\ \hspace{10cm}$
$x\ y_2\ +\ y_1\ =\ \frac{-\ 1}{x}[a\ Sin(log\ x)\ +\ b\ Cos(log\ x)]\ \hspace{10cm}$
$x\ y_2\ +\ y_1\ =\ \frac{-\ 1}{x}\ [y]\ ——-\ Using\ (1)\ \hspace{10cm}$
$x(x\ y_2\ +\ y_1)\ =\ y\ \hspace{10cm}$
$x^2\ y_2\ +\ x\ y_1\ =\ y\ \hspace{10cm}$
$x^2\ y_2\ +\ x\ y_1\ -\ y\ =\ 0\ \hspace{10cm}$
$\color {purple} {Example\ 12:}\ If\ y\ =\ \frac{cos\ x}{x}\ \color {red} {prove\ that\ x\ y_2\ +\ 2\ y_1\ +\ xy\ =\ 0}\ \hspace{10cm}$
$\color {blue}{Solution:}\ y\ =\ \frac{cos\ x}{x}\ \hspace{15cm}$
$xy\ =\ cos\ x\ —–\ (1)\ \hspace{15cm}$
$Differentiate\ both\ sides\ w.\ r.\ t.\ x\ \hspace{10cm}$
$\frac{d}{dx}(xy)\ =\ \frac{d}{dx}(cos x)\ \hspace{10cm}$
$x\ \frac{d}{dx}(y)\ +\ y\ \frac{d}{dx}(x)\ =\ -\ sin\ x\ \hspace{10cm}$
$xy_1\ +\ y\ (1)\ =\ -\ sin\ x\ \hspace{10cm}$
$xy_1\ +\ y\ =\ -\ sin\ x\ \hspace{10cm}$
$Again\ Differentiate\ w.\ r.\ t.\ x\ on\ both\ sides\ \hspace{10cm}$
$\frac{d}{dx}(xy_1\ +\ y)\ =\ -\ \frac{d}{dx}(sin x)\ \hspace{10cm}$
$\frac{d}{dx}(xy_1)\ +\ \frac{d}{dx}(y))\ =\ -\ cos\ x\ \hspace{10cm}$
$x\ \frac{d}{dx}(y_1)\ +\ y_1\ \frac{d}{dx}(x)\ +\ \frac{dy}{dx}\ =\ -\ cos\ x\ \hspace{10cm}$
$xy_2\ +\ y_\ (1)\ +\ y_1\ =\ -\ xy\ ——-\ Using\ (1)\ \hspace{10cm}$
$xy_2\ +\ y_1\ +\ y_1\ =\ -\ xy\ \hspace{10cm}$
$xy_2\ +\ 2\ y_1\ =\ -\ xy\ \hspace{10cm}$
$xy_2\ +\ 2\ y_1\ +\ xy\ =\ 0\ \hspace{10cm}$

Exercise Problems

$\LARGE{\color {purple} {PART- A}}$
$\color {purple} {1.}\ \color {red} {Find\ the\ order\ and\ degree\ of\ the\ differential\ equation}\ \frac{d^3y}{dx^3}\ -\ 5\ \frac{d^2y}{dx^2}\ +\ 6\ \frac{dy}{dx}\ +\ 7\ y\ =\ 0\ \hspace{10cm}$
$\color {purple} {2:}\ \color {red} {Find\ \frac{d^2y}{dx^2}}\ if\ y\ =\ x^2\ +\ 6\ x\ -\ 15\ \hspace{15cm}$
$\LARGE{\color {purple} {PART- B}}$
$\color {purple} {3.}\ \color {red} {Form\ the\ differential\ equation\ of}\ y^2\ =\ 4\ a\ x\ by\ eliminating\ the\ constant\ ‘a’\ \hspace{15cm}$
$\LARGE{\color {purple} {PART- C}}$
$\color {purple} {4:}\ If\ y\ =\ x^2\ cos\ x,\ \color {red} {prove\ that\ x^2\ y_2\ -\ 4\ x\ y_1\ +\ (x^2\ +\ 6)y}\ =\ 0\ \hspace{15cm}$
$\color {purple} {5:}\ If\ xy\ =\ a\ e^x\ +\ b\ e^{-x}\ \color {red} {prove\ that\ xy_2\ +\ 2\ y_1\ =\ xy}\ \hspace{15cm}$